Development of Jenga Collaboration with Combo Cards Learning Media on Ecosystem Material for Grade VII Students - Bayu Antrakusuma; Sri Ayu Finanda; Kadek Dwi Hendratma Gunawan; Suciati Suciati; Bayu Antrakusuma; Sri Ayu Finanda; Kadek Dwi Hendratma Gunawan; Budi Utami; Budi Utami (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
The low level of student engagement and collaboration in group-based science learning, particularly on the abstract topic of ecosystems, underlies this study. Preliminary observations at three junior high schools in Majenang District, Indonesia revealed limited use of interactive learning media that supports collaboration among students, consistent with data showing that 75% of students had not reached the Minimum Mastery Criteria (MMC) on ecosystem material. This study aims to develop the Jenga Collaboration with Combo Cards learning media and to examine its feasibility and effectiveness. The study employed a Research and Development (R&D) approach using the 4-D model (Define, Design, Develop, Disseminate), limited to the Develop stage. Data were collected through expert validation sheets, user-trial questionnaires, and pretest-posttest instruments, then analyzed through product validation, reliability testing, item difficulty and discriminating power analysis, statistical testing, and N-Gain analysis. The results show that the learning media was rated Highly Feasible based on Expert Judgement, with feasibility percentages of 84.44% (media expert), 85.45% (content expert), and 85.83% (instructional design expert). The Paired Samples T-Test yielded t = -9.377 with Sig. (2-tailed) = 0.000 < 0.05, indicating a significant effect between students' pretest (mean 44.29) and posttest (mean 70.00) scores. The mean N-Gain obtained was 0.47, categorized as Medium. These findings demonstrate that the Jenga Collaboration with Combo Cards learning media is feasible and effective for improving students' learning outcomes on ecosystem material in Grade VII.